Epidemiology of human papillomavirus infection in women from Xiamen, China, 2013 to 2023 - Yao, Xingmei; Li, Qing; Chen, Yu; Du, Zhuowen; Huang, Yanru; Zhou, Yixi; Zhang, Jian; Wang, Wenbo; Zhang, Lutan; Xie, Jieqiong; Xu, Chao; Ge, Yunsheng; et al. (Frontiers in Public Health, 2024)
Background: Cervical cancer is primarily caused by HPV infection. The epidemiology of HPV infection in specific areas is of great meaning of guide cervical cancer screening and formulating HPV vaccination strategies. Here, we evaluated the epidemiological characteristics of HPV infection in Xiamen population. Methods: In total, 159,049 cervical exfoliated cell samples collected from female outpatients in Women and Children's Hospital, School of Medicine, Xiamen between January 2013 and July 2023 were analyzed. HPV DNA detection was performed using HPV genotyping kits (Hybribio Limited Corp, China). An analysis was conducted on the prevalence of HPV infection, taking into account factors such as age, year, and multiple patterns of HPV infection. The differences in prevalence among age groups and years were compared using χ2 test. Results: The overall prevalence of any 21 HPV genotypes was 18.4%, of which the high-risk HPV (HR-HPV) positive rate was 14.6%. The age-specific prevalence of HPV infection showed a bimodal distribution, with two distinct peaks, one at <25 years (31.2%) and the other at 60-64 years (32.9%). There was a downward trend in the prevalence of HPV infection over time, decreasing from 26.2% in 2013 to 14.5% in 2021, and then increasing to 19.0% in 2023. The five most prevent HR-HPV genotypes were HPV52 (4.0%), 58 (2.6%), 16 (2.5%), 51 (1.8%), and 39 (1.7%). Among the positive cases, 76.7% were detected with only one genotype and 23.3% with multiple genotypes. The most common co-infection was HPV52 + HPV58 (0.24%), followed by HPV16 + HPV52 (0.24%), HPV52 + HPV53 (0.21%), HPV52 + HPV81 (0.21%), HPV51 + HPV52 (0.19%), HPV16 + HPV58 (0.18%), and HPV39 + HPV52 (0.17%). Conclusions: The study provided the largest scale information on the recent epidemiological characteristics of HPV infection in Xiamen, and even in Fujian Province, China, which would support making the prevention and control strategies for cervical cancer in the region.